Peran Elit Desa Dalam Pengembangan Wellness Tourism Di Desa Adat Bindu, Desa Mekar Bhuana, Kecamatan Abiansemal, Kebupaten Badung - Savitri, Ni Wayan Gita Sadhana; Arida, I Nyoman Sukma (JURNAL DESTINASI PARIWISATA, 2019)
Bindu Village is located at Badung district, which has potency to develop the wellness tourism. Development wellness tourism at Bindu village involves the elite people. The purpose of this study was to identify tourist attractions and the role of elite people in developing wellness tourism at Bindu village. Data collection techniques conducted in this study are observation techniques, interview techniques and documentary techniques. The determination technique of informant uses the purposive sampling technique. Data analysis technique used is qualitative data analysis technique. The results of the discussion that can be concluded is wellness tourism activities by doing healer activities, purification and therapy. Bindu Village has tourism potency such as the natural potential, the cultural potential and the artificial potential. The role of elite people in the development of wellness tourism in Bindu village is carried out by developing those potencies, building tourism facilities and promotions.   Keywords: role, elite people , wellness tourism